Pengembangan E-LKPD Interaktif Pada Materi Hidrolisis Garam Dengan Model Problem Based Learning - Dessy Analinta; Abudarin, Abudarin; Fatah, Abdul Hadjranul (Jurnal Ilmiah Kanderang Tingang, 2025)
This research aims to determine the feasibility of interactive e-LKPD and the effectiveness of using interactive e-LKPD with the PBL model on salt hydrolysis subject. The development of interactive e-LKPD uses the 4-D model from Thiagarajan with development stages including define, design, develop and disseminate. Technically, the development stages carried out include problem identification, student needs analysis, material analysis, initial e-LKPD design, expert assessment, individual readability tests, group readability tests, and field trials. The subjects of this research were students of class XI MIPA SMAN 1 Palangka Raya. Data collection is through validation questionnaires, as well as pre-test and post-test question sheets. Interactive e-LKPD with the PBL model is very effective in guiding students' learning activities with a success percentage of 93.01%. The effectiveness of interactive e-LKPD with the PBL model to increase students' conceptual understanding is in the high category with an N-Gain score of 0.87. The ability to learn using e-LKPD with the PBL model is positively correlated with concept understanding (r = 0.950) with a coefficient of determination of 90.34%. Based on these feasibility criteria, interactive e-LKPD with a PBL model on salt hydrolysis subjet is suitable for use and effective in increasing students' understanding.